2008
DOI: 10.1371/journal.pone.0002409
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution Generates a Novel Oncolytic Virus for the Treatment of Colon Cancer

Abstract: BackgroundViral-mediated oncolysis is a novel cancer therapeutic approach with the potential to be more effective and less toxic than current therapies due to the agents selective growth and amplification in tumor cells. To date, these agents have been highly safe in patients but have generally fallen short of their expected therapeutic value as monotherapies. Consequently, new approaches to generating highly potent oncolytic viruses are needed. To address this need, we developed a new method that we term “Dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
190
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(196 citation statements)
references
References 52 publications
6
190
0
Order By: Relevance
“…[43][44][45] Using 'directed evolution' or 'accelerated evolution' strategies, ColoAd1 and other crHAdVs have been generated which appear to be more potent than their parental HAdV-5 based vectors. 46,47 A total of 458 clinical trials employing HAdV-mediated gene therapy have been reported to date. ONYX-015, H101 (Oncorine) and other first-generation oncolytic crHAdVs have gone through several phase I/II trials without relevant signs of high grade toxicity but also without significant therapeutic effects, resulting in discontinuation of further trails.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
“…[43][44][45] Using 'directed evolution' or 'accelerated evolution' strategies, ColoAd1 and other crHAdVs have been generated which appear to be more potent than their parental HAdV-5 based vectors. 46,47 A total of 458 clinical trials employing HAdV-mediated gene therapy have been reported to date. ONYX-015, H101 (Oncorine) and other first-generation oncolytic crHAdVs have gone through several phase I/II trials without relevant signs of high grade toxicity but also without significant therapeutic effects, resulting in discontinuation of further trails.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
“…We therefore decided to use an immunodeficient mouse model with liver metastases derived from human colon cancer HT-29 cells. HT-29 cells secrete carcinoembryonic antigen (CEA), and serum CEA levels in mice directly correlate with the tumor burden, as we have shown in one study (Kuhn et al, 2008). As a model oncolytic adenovirus, we used Ad5= 35.IR.E1A=TRAIL (Sova et al, 2004).…”
Section: Figmentioning
confidence: 99%
“…Importantly, pretreatment of mice with X-bp greatly increased the therapeutic effect of Ad5=35.IR-E1A=TRAIL as reflected in CEA levels and tumor burden ( p < 0.001). Because, previously, an Ad5-based oncolytic vector (ONYX-015) did not exert a significant antitumor effect in the HT-29 liver metastasis model (Kuhn et al, 2008), we did not include an Ad5-based vector in this study.…”
Section: Figmentioning
confidence: 99%
“…1 In addition, they have the ability to circulate within the body, making the treatment of both primary and metastatic lesions possible. However, to date, oncolytic viruses have yet to reach their full potential as an effective new class of anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…1 This virus has been shown to have superior potency over its parental viruses in vitro (on a panel of tumor cell lines), ex vivo (on patient tumor explants) and in vivo (in a liver metastasis colon cancer model). Although ColoAd1 has shown a high degree of selectivity and safety in all studies that have been carried out to date, these are artificial systems that may not fully mimic the conditions in a cancer patient.…”
Section: Introductionmentioning
confidence: 99%